1984
DOI: 10.2307/526581
|View full text |Cite
|
Sign up to set email alerts
|

The Temple of Claudius at Colchester Reconsidered

Abstract: T HE recognition by R. E. M. Wheeler in 1920 that the massive Norman keep at Colchester encapsulated the podium of the Temple of Claudius stimulated Dr P. G. Laver, his collaborator in an earlier study of the colonia, 1 to excavate in and around the keep during the 1920's and 30's. Some of the results were published by the late Rex Hull in Roman Colchester (1958). At the time of Hulj's death in 1976, the writer was preparing the drawings to accompany a paper 2 which included a summary report by Hull on the exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Insert Figure 3 here The first public buildings at Colchester were constructed in the area of the fortress annexe outside the main fortress, probably because the fortress was too crowded, and this may be the reason why the defences were levelled. This conversion and construction process, however, was not speedy and may have taken a number of years, since excavations indicated that the fortress ditch had been neglected for some time before it was levelled (Crummy 1988: 42); the Temple of Claudius, moreover, may well not have been begun until Claudius' death in AD 54, although this need not necessarily have been the case (Drury 1984). Like Gloucester, the defences of the fortress were maintained at Lincoln, and there was probably a fairly similar process of conversion (M. J.…”
Section: Town Construction Processesmentioning
confidence: 99%
“…Insert Figure 3 here The first public buildings at Colchester were constructed in the area of the fortress annexe outside the main fortress, probably because the fortress was too crowded, and this may be the reason why the defences were levelled. This conversion and construction process, however, was not speedy and may have taken a number of years, since excavations indicated that the fortress ditch had been neglected for some time before it was levelled (Crummy 1988: 42); the Temple of Claudius, moreover, may well not have been begun until Claudius' death in AD 54, although this need not necessarily have been the case (Drury 1984). Like Gloucester, the defences of the fortress were maintained at Lincoln, and there was probably a fairly similar process of conversion (M. J.…”
Section: Town Construction Processesmentioning
confidence: 99%
“…Other major advances at this time were the aerial photograph surveys by Ida McMaster at Gosbecks, which revealed more of the late Iron Age/Roman field systems, and in 1976 the discovery by David Wilson of the Committee for Aerial Photography at the University of Cambridge and, independently, by John Hampton of the National Monuments Record, of a Roman fort at Shrub End. The churches of the town also received some attention (Rodwell and Rodwell 1977, 24-41), as did the castle and the Temple of Claudius Drury 1984).…”
Section: The Colchester Archaeological Trustmentioning
confidence: 99%
“…However, amphitheatres had larger arenas than theatres and would have been less suited to religious displays and acts. Also, while theatres in Britain (at Gosbecks ;Hull 1958;Dunnett 1971;Drury 1980: at Verulamium;Kenyon 1934 and at Colchester;Drury 1984) are closely associated with temple buildings, amphitheatres are commonly military (as at Caerleon;Wheeler and Wheeler 1928: Chester;Thompson 1975: Charterhouse on Mendip;Gray 1909 and Tomen-y-Mur;Gresham 1938) or urban (see n. 3) in context. Consequently it would seem necessary to argue one of the following for Frilford: a) the amphitheatre is military, b) the amphitheatre is associated with a settlement of urban status rather than with the temple, c) the amphitheatre is associated with the temple and is a crude replacement for the typical Gallic form of amphitheatrekheatre.…”
Section: The Status Of the Religious Complex At The Noah's Ark Innmentioning
confidence: 99%